Convert Contraceptive use among women of reproductive age in Ibadan, Nigeria (2019)
BACKGROUND: This study assessed the prevalence and determinants of covert contraceptive use among women of reproductive age in Ibadan, Nigeria. METHODS: A cross sectional study among women attending a family planning clinic in a maternity teaching hospital in Ibadan, Nigeria was conducted. Data was collected on sociodemographic characteristics, contraceptive use and partner awareness of use. The socio-demographic predictors of covert contraceptive use were explored using logistic regressions. RESULTS: Twenty-five (6.8%) of the 365 respondents were practicing covert contraception. Their mean age was 34.7+6.67 years, 98.6% were married and with modal parity of 3 (29.6%). A logistic regression analysis showed that participants' age (p = 0.555), occupation (p = 0.679), education (p = 0.642), parity (p = 0.385) and husbands' education (p = 0.926) were not statistically associated with covert contraceptive use while husbands' financial supports (p = 0.000) and approval for family planning use (p = 0.000) were associated with reduction in the likelihood covert contraceptive use. CONCLUSIONS: Covert contraceptive use exist among our women. Poor financial support and disapproval by the husbands were the strongest predictors of the practice. Greater male involvement in contraceptive service provision will help address these negative factors promoting covert contraceptive practices.